Cerebral Ischemia or Intrauterine Inflammation Promotes Differentiation of Oligodendroglial Precursors in Preterm Ovine Fetuses: Possible Cellular Basis for White Matter Injury - Saito, Masatoshi; Watanabe, Shinpei; Hanita, Takushi; Matsuda, Tadashi; Kobayashi, Yoshiyasu; Watanabe, Tatsuya; Kitanishi, Ryuta (The Tohoku Journal of Experimental Medicine, 2014)
White matter injury in premature infants is known to be major cause of long-term neurocognitive disability, but the pathogenic mechanism remains unclear, hampering our ability to develop preventions. Periventricular leukomalacia is a severe form of white matter injury. In the present study, we explored the effects of cerebral ischemia and/or intrauterine inflammation on the development of oligodendroglia in the cerebral white matter using chronically instrumented fetal sheep. Each fetus received one of three insults: hemorrhage, inflammation and their combination. In the hemorrhage group, 40% of the fetoplacental blood volume was acutely withdrawn, and 24 hours after removal, the blood was returned to the fetus. The inflammation group received intravenous granulocyte-colony stimulating factor and intra-amniotic endotoxin and thus suffered from necrotizing funisitis and chorioamnionitis. The inflammatory hemorrhage group underwent acute hemorrhage under the inflammatory state. The sham group received no insults. Importantly, periventricular leukomalacia was not detected in the sham and the inflammation groups. Differentiating oligodendroglia at various developmental stages were identified by immunohistochemical analysis with specific antibodies. No difference in the density of oligodendroglial progenitors was detected among the four groups, whereas oligodendroglial precursors were significantly reduced in the three insult groups, compared to sham control. Moreover, the density of immature oligodendroglia was higher in the inflammation group and the inflammatory hemorrhage group, while the density of mature oligodendroglia was highest in the hemorrhage group. We propose that cerebral ischemia or intrauterine inflammation induces the differentiation of oligodendroglial precursors in preterm fetuses, eventually resulting in their exhaustion.